THU0620 THE PHYSIOLOGICAL FINGER JOINT ARCHITECTURE – AGE-RELATED INCREASE OF EROSIONS AND OSTEOPHYTES IN THE JOINTS OF HEALTHY INDIVIDUALS. (June 2019) - Simon, David; Berlin, Andreas; Tascilar, Koray; Bayat, Sara; Engelke, Klaus; Rech, Jürgen; Figuereido, Camille; Hueber, Axel; Schett, Georg; Kleyer, Arnd
Abstract : Background: The "normal" finger joint architecture has not yet been defined and could change in the course of life. Therefore the objective was to assess the physiological finger joint architecture of healthy individuals and the relation of structural changes to age and sex. Objectives: Therefore the objective was to assess the physiological finger joint architecture of healthy individuals and the relation of structural changes to age and sex using high-resolution quantitative computed tomography (HR-pQCT) of the hands. Methods: Healthy individuals without rheumatic diseases and other comorbidities were recruited through a field campaign and received HR-pQCT examination of the Metacarpophalangeal 2/3 and Proximal Interphalangeal 2/3 joints of one hand. The number of erosions and osteophytes was quantified across different sexes and age decades (6 decades within the age range of 21-80 years). 1, 2, 3 Results: 120 healthy individuals (10 women and 10 men in each decade) were recruited. Bone erosions [median (Q1-Q3), 1 (0-2)] and osteophytes [2 (1-4)] were found in both sexes without significant differences. However, structural changes increased with age: the overall incidence rate ratio (IRR) for the number of erosions and osteophytes per age were 1.04 (95% CI 1.03-1.06; 95% CI 1.03-1.05), which indicates a 4% increase in the number of erosions and osteophytes per year. The use of the 3 rd decade as the reference demonstrated that healthy individuals in the age decades from 50 years had higher IRR for erosion number (6 th, 7 th, 8 th decade: 4.87 (2.20-11.75), 6.81 (3.08-16.46) and 6.92 (3.11-16.79)) compared to younger subjects (4 th, 5 th decade: 1.80 (0.69-4.87), 1.53 (0.59-4.10)). The IRRs of osteophytes also indicate a progressive increase after the fifth decade, with IRRs of 2.32 (1.32-4.17), 4.17 (2.38-7.49) and 6.86 (3.97-12.20) for the 6 th, 7 th and 8 th decades, respectively. Conclusion: Structural changes in the finger joints of healthy individuals are age-related. While being rare under 50 years of age, erosions and osteophytes accumulate above the age of 50, suggesting that the threshold between "normal" and "pathological" shifts with increasing age. References: [1] Simon D, Kleyer A, Stemmler, et al. Age- and Sex-Dependent Changes of Intra-articular Cortical and Trabecular Bone Structure and the Effects of Rheumatoid Arthritis. J Bone Miner Res. 2017Apr [2] Figueiredo CP, Simon D, Englbrecht M, et al. Quantification and Impact of Secondary Osteoarthritis in Patients With Anti-Citrullinated Protein Antibody-Positive Rheumatoid Arthritis. Arthritis Rheumatol. 2016 Sep [3] Figueiredo CP, Kleyer A, Simon D, et al. Methods for segmentation of rheumatoid arthritis bone erosions in high-resolution peripheral quantitative computed tomography (HR-pQCT). Semin Arthritis Rheum. 2018Apr; Disclosure of Interests: David Simon Grant/research support from: Novartis, Consultant for: Lilly, Speakers bureau: Janssen, Andreas Berlin: None declared, Koray Tascilar: None declared, Sara Bayat: None declared, Klaus Engelke: None declared, Jürgen Rech Grant/research support from: Bristol-Myers Squibb and Celgene (greater than $10, 000), Consultant for: Bristol-Myers Squibb, Celgene, Chugai, GlaxoSmithKline, Janssen, Eli Lilly, Novartis, Roche, Sanofi Aventis, and UCB (in total more than $10, 000), Speakers bureau: Bristol-Myers Squibb, Celgene, Chugai, GlaxoSmithKline, Janssen, Eli Lilly, Novartis, Roche, Sanofi Aventis, and UCB (in total more than $10, 000), Camille Figuereido: None declared, Axel Hueber Grant/research support from: Novartis, Pfizer, Lilly, Consultant for: Lilly, GSK, Novartis, Janssen, Celgene, Abbvie, Roche, Speakers bureau: Lilly, Janssen, Novartis, Celgene, Biogen, Abbvie, BMS, Georg Schett: None declared, Arnd Kleyer Grant/research support from: Lilly, Consultant for: Lilly, Speakers bureau: Abbvie